Design, structural characterization and cytotoxic properties of copper(I) and copper(II) complexes formed by vitamin B3 type. (14th December 2017) - Anacleto, Beatriz; Gomes, Pedro; Correia-Branco, Ana; Silva, Cláudia; Martel, Fátima; Brandão, Paula
Graphical abstract: Four new copper complexes containing vitamin B3 type have been synthesized, and evaluated for their antitumor capacity in vitro against a Caco-2 cell line. All complexes inhibited the growth of these cells, although the complex combining vitamin B3 and 1, 10-phenanthroline is significantly more effective (with an IC50 value of 30 (24–38) µM). Abstract: Four new examples of copper complexes [Cu(L1)2 (H2 O)4 ](1), [Cu(HL1)2 (H2 O)2 ](NO3 )2 (2), [Cu(HL1)Cl]∞ (3), [Cu(HL2)(phen)(H2 O)](NO3 )·3(H2 O)(4) with HL1 = vitamin B3, H2 L2 = 2-hydroxy-vitamin B3, phen = 1, 10-phenanthroline, were synthesized and their structures solved by single crystal X-ray diffraction. For all complexes, vitamin B3 acts as monodentate ligand through the N atom from pyridyl group or the oxygen atom from the carboxylate group. The copper centers exhibit different geometries, namely octahedral (1), square planar (2), tetrahedral (3) and square pyramidal (4). Intermolecular π⋯π interactions as well as an H-bonding network were observed for all complexes. The antitumor capacity of the complexes was tested in vitro against a human cancer cell line, the colorectal adenocarcinoma (Caco-2) cell line, by determining their effect on cell viability, using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide as reagent. Noteworthy, complex of copper(II) with hydroxyl-vitamin B3 and phenanthroline(4) showed a considerable lower IC50 value (30 (24–38) μM), when compared with vitamin B3, phenanthroline and cisplatin against the same cell line.